The Effect of Boron and Soaking on Germination of Sandalwood ( Santalum album Linn. ) Seed - Supriyanto Supriyanto; Selly Maurina Amin; Benny Subandi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
haracteristic of sandalwood germination is very slow,it is due to seed coat thickness (seed coat dormancy). Boron is an important nutrient that is required to improve the seed germination and vigor. The aim of this research was to test the effectiveness of boron in various concentrations and period of soaking to speed up the seed germination. The experimental design of research was factorial in Completely Randomized Design (CRD). The results of this research showed that the initial treatment of sandalwood seed in boron soaking on 400 ppm concentration could accelerate the sandalwood seed germination one week earlier with 42% germination percentage while control was 34.6%. The optimal soaking of sandalwood seeds in boron was 24 hours.